Etiological patterns of bacterial meningitis in neonatal sepsis - Andy Setiawan; Idham Amir; Alan R. Tumbelaka (Paediatrica Indonesiana, 2006)
Background Sepsis and meningitis are major causes of mortalityand morbidity in neonates. The prevalence of sepsis is around 1-4out of every 1000 live births, and one-fourth is accompanied bymeningitis. These numbers are higher in prematures.Objective To find out the prevalence and etiological patterns ofbacterial meningitis in neonatal sepsis, and the pattern of antibi-otic susceptibility for organisms causing bacterial meningitis.Methods This was a cross sectional study, conducted in the neo-natal ward and emergency room at Cipto Mangunkusumo Hospi-tal from October 2003 to October 2004.Results Seventy two neonates fulfilled the inclusion criteria andwere examined for blood and cerebrospinal fluid (CSF) cultures.Sixty out of 72 neonates were proven for sepsis. Bacterial menin-gitis was found in 18 neonates, and all cases were accompaniedby sepsis. Positive CSF cultures were found in 12 neonates. Theother six were diagnosed based on CSF cell count >32/Î¼l.Acinetobacter calcoaceticus was the major causative organismsin this study. The organisms were highly resistant to first line anti-biotics, except for chloramphenicol. They were also sensitive toceftazidime (second line), meropenem, and imipenem.Conclusions The prevalence of bacterial meningitis in neonatalsepsis at Cipto Mangunkusumo Hospital was 18/60 in 2003-2004.The major causative organism was Acinetobacter calcoaceticus.Antibiotic resistance was very high and only chloramphenicol,ceftazidime, meropenem, and imipenem remain effective